Sustainable development versus sustainable biosphere - Rolston, Holmes, 1932-2025, speaker (Colorado State University. Libraries, 2009)
In sustainability debates, there are two poles, complements yet opposites. Economy can be prioritized, with the environment contributory to economics at the center. This is sustainable development, widely advocated, including statements by the United Nations. At the other pole, the environment is prioritized. A sustainable biosphere model demands a baseline quality of environment, respect for the integrity of natural systems. The economy must be worked out within such quality of life in a quality environment. This is advocated by the Ecological Society of America. Neither economics nor ecology is well equipped to analyze this issue ethically.
Sustainable development vs. sustainable biosphere
A lecture given at the American Association for the Advancement of Science, Annual Meeting, 2009, Chicago: Our Planet and Its Life: Origins and Futures.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: environmental conservation; sustainable biosphere; sustainability; sustainable development; UNCED; United Nations conference on environment and development; Ecological Society of America